1944
DOI: 10.3181/00379727-55-14492
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Breeding on Induction of Mammary Cancer with Methylcholanthrene in Strain Dba Female Mice.

Abstract: From t'he Departments of Anatomy, Radiology, and Phgsiology,S ~'~t i r c r s i t y of MinnesotaThe percutaneous administration of either 9,10dimethyl-l,2-benzanthracene or methylcholanthrene was reported by Engelbreth-Holm and Lefbvrel and Engelbreth-Holm* to accelerate the development of mammary cancer in female mice of strain Dba. Morton and Mider3v4 had previously treated similar mice in like manner, but had not described this phenomenon. The latter authors stated specifically3 that male and female animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1946
1946
1964
1964

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Experiments carried out by Mider and Morton (1939), Bonser and Orr (1939), Strong and Smith (1939), Bonser (1940), Strong and Williams (1941), Engelbreth-Holm (1941), Engelbreth-Holm and Lefevre (1941), Orr (1943), Kirschbaum, Lawrason, Kaplan and Bittner (1944), Kirschbaum, Williams and Bittner (1946), Shimkin and Bryan ), Strong (1945), Orr (1946, demonstrated that carcinogenic hydrocarbons induce the appearance of breast cancer in females of low-cancer strains or accelerate the development of breast tumours in female mice of high-cancer strains. In these experiments it was also shown that oestrogenic influence is important in the induction of breast cancer by carcinogenic hydrocarbons, since mice developing these tumours in the absence of treatment with oestrogens were females, with one exception, a CBA male (Orr, 1943).…”
mentioning
confidence: 99%
“…Experiments carried out by Mider and Morton (1939), Bonser and Orr (1939), Strong and Smith (1939), Bonser (1940), Strong and Williams (1941), Engelbreth-Holm (1941), Engelbreth-Holm and Lefevre (1941), Orr (1943), Kirschbaum, Lawrason, Kaplan and Bittner (1944), Kirschbaum, Williams and Bittner (1946), Shimkin and Bryan ), Strong (1945), Orr (1946, demonstrated that carcinogenic hydrocarbons induce the appearance of breast cancer in females of low-cancer strains or accelerate the development of breast tumours in female mice of high-cancer strains. In these experiments it was also shown that oestrogenic influence is important in the induction of breast cancer by carcinogenic hydrocarbons, since mice developing these tumours in the absence of treatment with oestrogens were females, with one exception, a CBA male (Orr, 1943).…”
mentioning
confidence: 99%